1996
DOI: 10.1002/j.1834-4453.1996.tb00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Sand tempers in indigenous Lapita and Lapitoid Polynesian Plainware and imported protohistoric Fijian pottery of Ha'apai (Tonga) and the question of Lapita tradeware

Abstract: The Lapita site at Faleloa on Foa Island in the Ha'apai Group of central Tonga lies near the southeastern end of the belt of Lapita sites spread through island Melanesia and western Polynesia during the millennium 1500–500 BC. Temper sands in Faleloa Lapita sherds closely resemble modern placer sands on beaches of islands within Ha'apai, and document local manufacture without intrusion of tradeware. Other Lapita and Lapitoid (Polynesian Plainware) sherds from nearby islands in Ha'apai contain similar local tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…Preliminary petrographic study (15) of the tan-paste sherds erroneously suggested a Tongan origin for the tempers from the pyroxene-rich character of the sands. Subsequent work (16,17) has shown that Tongan placer sands and sherd tempers uniformly lack hornblende, but contain significant orthopyroxene (opx) as well as clinopyroxene (cpx). Pyroxene index (18), defined as cpx͞(cpx ϩ opx), lies in the range 0.82-0.89 for Tongan placer sands and sherd tempers of Ha'apai, Tongatapu, and Niuatoputapu (Fig.…”
mentioning
confidence: 99%
“…Preliminary petrographic study (15) of the tan-paste sherds erroneously suggested a Tongan origin for the tempers from the pyroxene-rich character of the sands. Subsequent work (16,17) has shown that Tongan placer sands and sherd tempers uniformly lack hornblende, but contain significant orthopyroxene (opx) as well as clinopyroxene (cpx). Pyroxene index (18), defined as cpx͞(cpx ϩ opx), lies in the range 0.82-0.89 for Tongan placer sands and sherd tempers of Ha'apai, Tongatapu, and Niuatoputapu (Fig.…”
mentioning
confidence: 99%
“…A major conclusion is that most of the pottery made during Pacific prehistory was manufactured locally. Yet in particular assemblages there are often low proportions of exotic sherds for which temper analysis has been used to help determine ancient trade or migration routes (Burley et al 2001;Dickinson 2001;Dickinson et al 1996;Ladefoged et al 1998). To this end, 45 dentate-stamped sherds from the Naitabale Lapita site were thin-sectioned and subjected to temper analysis.…”
Section: Potterymentioning
confidence: 99%
“…The integrating symbols may also indicate the successful acquirement of the right to use face motifs inherited from two different house-based groups through marriage, adoption, or even conquest. New Caledonian sherds have been found in the Loyalty Islands (Galipaud 1990, Sand 1995, and Vanuatu (Dickinson 1971;, a pattern that indicates some degree of local or even long-distance exchange along with the specialisation of pottery production (Dickinson et al 1996). The integration of face motifs may represent the achievement of a local community leader or leaders enhancing their collaborative resources and thereby potentially gaining some advantage in relationships with other communities.…”
Section: Spatial and Temporal Distribution Of Face Motifs At Lapita (mentioning
confidence: 99%
“…Lapita pottery was mostly manufactured by a uniform method of slabbuilding, strengthened with paddles and anvils, smoothed and decorated with various techniques, then fired at low temperatures (Bellwood 1978:258;Green 1974;. Chemical and petrographic studies from a number of Lapita sites indicate that there was no strict control over raw materials used to produce these pots and there is a lack of restricted correlation between tempers and motifs ( Island, (Kirch 1988a;Kirch 1991;, most Lapita pottery has been identified as having been locally made, and exchanged only among nearby local communities (Dickinson et al 1996;Galipaud 1990;). …”
Section: Introductionmentioning
confidence: 99%